2015
DOI: 10.1016/j.jsbmb.2014.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Biological messiness vs. biological genius: Mechanistic aspects and roles of protein promiscuity

Abstract: In contrast to the traditional biological paradigms focused on ‘specificity’, recent research and theoretical efforts have focused on functional ‘promiscuity’ exhibited by proteins and enzymes in many biological settings, including enzymatic detoxication, steroid biochemistry, signal transduction and immune responses. In addition, divergent evolutionary processes are apparently facilitated by random mutations that yield promiscuous enzyme intermediates. The intermediates, in turn, provide opportunities for fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 73 publications
(78 reference statements)
1
38
0
Order By: Relevance
“…Robust signaling pathways must not only respond to activating ligands but must discriminate against the wrong ones to reduce noise (50). For LRH-1, this challenge is amplified because its ligands include highly abundant intact PLs that include a large fraction of cell membranes.…”
Section: Discussionmentioning
confidence: 99%
“…Robust signaling pathways must not only respond to activating ligands but must discriminate against the wrong ones to reduce noise (50). For LRH-1, this challenge is amplified because its ligands include highly abundant intact PLs that include a large fraction of cell membranes.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data have suggested that a large number of enzymes can catalyse more than one chemical transformation. This phenomenon, referred to as enzyme “promiscuity”, is now considered as being the rule rather than the exception (Atkins, ; Khersonsky & Tawfik, ). It is believed to have played a central role in the evolution of enzymatic functions across several protein superfamilies, because promiscuous activities can rapidly be enhanced with a limited number of mutations (Glasner, Gerlt, & Babbitt, ).…”
Section: How Slow Is Rubisco?mentioning
confidence: 99%
“…The growth of wild-type (black curve), DmurI (red curve) and murI gene complemented strains (mustard curve) supplemented with 10 mM D-alanine. D-amino acid transaminase (D-AAT) from Mycobacterium smegmatis 207 for many enzymes is now well recognized (O'Brien and Herschlag, 1999;Khersonsky et al, 2006;Atkins, 2015).…”
Section: Discussionmentioning
confidence: 99%